2015
DOI: 10.1007/s10592-015-0757-6
|View full text |Cite
|
Sign up to set email alerts
|

Limited genetic structure in a wood frog (Lithobates sylvaticus) population in an urban landscape inhabiting natural and constructed wetlands

Abstract: Urbanization has been linked to amphibian population declines globally. Habitat fragmentation can negatively impact gene flow among populations but what role artificially constructed wetlands have in maintaining gene flow in urban amphibian populations remains uncertain. We assessed gene flow in a population of wood frogs (Lithobates sylvaticus) inhabiting both constructed and natural wetlands located in Edmonton, Alberta, Canada. We genotyped 10 microsatellite loci in 182 frogs from eight wetlands and tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 62 publications
2
23
1
Order By: Relevance
“…), while in the wood frog ( Lithobates sylvaticus ; Furman et al . ) diversity levels were very similar to those observed in our study. In Oviedo, fire salamander populations are putatively isolated to a greater extent than these species (see below), making the observed genetic diversity even more surprising.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…), while in the wood frog ( Lithobates sylvaticus ; Furman et al . ) diversity levels were very similar to those observed in our study. In Oviedo, fire salamander populations are putatively isolated to a greater extent than these species (see below), making the observed genetic diversity even more surprising.…”
Section: Discussionsupporting
confidence: 90%
“…Other studies in urban‐dwelling amphibians have found a global F ST that varies considerably across different systems, being much lower in moor frogs on Montréal Island (Noël & Lapointe ) and in the red‐backed salamander ( Plethodon cinereus ; Furman et al . ) but quite high in the stream‐dwelling northern dusky salamander ( Desmognathus fuscus ) in New York, where population extirpation and degradation of streams likely led to a marked decrease in genetic diversity as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, Furman et al. () found no evidence of genetic erosion and increased genetic differentiation in natural and artificially constructed wetlands in a wood frog, despite extensive urbanization. In the same way, isolated urban populations of the Fire salamander did not exhibit lower levels of genetic diversity and showed similar N e compared to rural populations (Lourenço et al., ).…”
Section: Discussionmentioning
confidence: 93%
“…Urban environments can host trapped and isolated populations. In this context, recent studies investigated the strength of genetic drift induced by reduced functional connectivity across an urban matrix (e.g., Beninde et al., ; Furman, Scheffers, Taylor, Davis, & Paszkowski, ; Lourenço et al., ; Munshi‐South, Zak, & Pehek, ). However, it appears that new anthropogenic habitats can also promote the establishment of pioneer species in highly disturbed areas (Amici et al., ; Flavenot, Fellous, Abdelkrim, Baguette, & Coulon, ).…”
Section: Introductionmentioning
confidence: 99%